Understanding international conflicts : an introduction to theory and history - Nye, Joseph S. (New York : Longman, 2000)
Written by one of the most distinguished scholars and lecturers in the field, Understanding International Conflicts is a text students enjoy reading, helping them to understand and think about the complex domain of international politics. The book deftly balances theory and history to help students develop a well-rounded, informed framework for analyzing current issues and dilemmas. Updated with the most recent scholarship, the third edition explores the international issues confronting us as we enter the 21st century. Understanding International Conflicts aims to provide students with the conceptual tools that will help them shape their own answers to the unfolding developments in our world long after exams are done. -- from http://www.abebooks.com (August 16, 2011).
Preface -- 1. Is There an Enduring Logic of Conflict in World Politics? -- 2. Origins of the Great Twentieth-Century Conflicts -- 3. Balance of Power and World War I -- 4. The Failure of Collective Security and World War II -- 5. The Cold War -- 6. Intervention, Institutions, and Regional Conflicts -- 7. Interdependence and Power -- 8. A New World Order? -- Credits -- Index.
Includes bibliographical references and index.
Keywords: 1900-1999; International relations; War (International law); World politics -- 20th century; Relations internationales